Assessing Fintech Awareness and Knowledge Among Students at Selected Universities in Somalia - Awale, Abdirahman Abdinur; Kulmie, Dayah Abdi (International Journal of Economics and Financial Issues, 2024)
This study examines financial technology awareness among students at four Mogadishu universities (Jamhuriya University of Science and Technology, Banadir University, SIMAD University, and the University of Somalia), using a cross-sectional descriptive research design. The study utilized a structured questionnaire to evaluate 231 students’ understanding and familiarity with fintech concepts, focusing on demographic factors and perceived curriculum gaps. The study’s participants were diverse in gender, age, institution, major, and year of study. The majority were male (63%), with 78% aged between 20 and 25. The study reveals that students’ familiarity and understanding of fintech concepts like blockchain, smart contracts, neo- banking, crowdfunding, cloud computing, big data analytics, robo-advisors, and AI are low. This highlights significant gaps in students’ knowledge of critical areas digital finance, e-payments or e-banking. The study shows a moderate correlation between demographic factors and students’ fintech awareness, with 13.9% of variation explained by these factors. The overall model is statistically significant (F = 7.265, P < 0.001), indicating that these factors collectively impact students’ knowledge and awareness of fintech. Gender, age, and university attended do not significantly influence fintech awareness, suggesting they are not major determinants. However, the study reveals that students’ awareness of fintech increases as they progress through their academic years, with certain majors showing higher levels of awareness. The study recommends universities incorporate fintech topics into their courses, develop accessible options, invest in resources, collaborate with fintech companies, strengthen industry partnerships, and offer cross-disciplinary electives.